2022
DOI: 10.1590/s0004-2803.202203000-71
|View full text |Cite
|
Sign up to set email alerts
|

Genes Expression and Serum Biomarkers for Diagnosis of Hepatocellular Carcinoma, Cirrhosis and Hepatitis C

Abstract: Background: Hepatocellular carcinoma (HCC) is the most common type of liver cancer. Risk factors for HCC include hepatitis C (HCV) and B (HBV) virus infection, alcoholic cirrhosis and genetic alterations that can affect several cellular pathways. Objective: This study purposed to analyze the gene and serum protein expression of vascular endothelial growth factor (VEGF), angiogenesis, alpha fetoprotein, cystatin B (CSTB), β-catenin and glypican-3 (GPC3) in groups with HCC, cirrhosis or HCV and controls, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The authors suggested that HOMA IR could be a valuable tool to identify those patients with non-alcoholic steatohepatitis, but prospective validation and comparison of HOMA IR with other readily available non-invasive markers of fibrosis in the Brazilian population is still an unmet need. Fernandes Ferreira et al (15) , on the other hand, have investigated serum and gene expression of several markers of angiogenesis and cell differentiation in subjects with HCC. The authors have correlated overexpression of vascular endothelial growth factor and alpha fetoprotein in liver tissue of subjects with HCC, particularly in those with advanced stages according to BCLC classification.…”
mentioning
confidence: 99%
“…The authors suggested that HOMA IR could be a valuable tool to identify those patients with non-alcoholic steatohepatitis, but prospective validation and comparison of HOMA IR with other readily available non-invasive markers of fibrosis in the Brazilian population is still an unmet need. Fernandes Ferreira et al (15) , on the other hand, have investigated serum and gene expression of several markers of angiogenesis and cell differentiation in subjects with HCC. The authors have correlated overexpression of vascular endothelial growth factor and alpha fetoprotein in liver tissue of subjects with HCC, particularly in those with advanced stages according to BCLC classification.…”
mentioning
confidence: 99%